The complexities of investigating mitochondria dynamics in multiple sclerosis and mouse models of MS - Atkinson, Kelley C.; Osunde, Marvellous; Tiwari-Woodruff, Seema K. (Frontiers in Neuroscience, 2023)
Multiple sclerosis (MS) is a demyelinating, degenerating disorder of the central nervous system (CNS) that is accompanied by mitochondria energy production failure. A loss of myelin paired with a deficit in energy production can contribute to further neurodegeneration and disability in patients in MS. Mitochondria are essential organelles that produce adenosine triphosphate (ATP) via oxidative phosphorylation in all cells in the CNS, including neurons, oligodendrocytes, astrocytes, and immune cells. In the context of demyelinating diseases, mitochondria have been shown to alter their morphology and undergo an initial increase in metabolic demand. This is followed by mitochondrial respiratory chain deficiency and abnormalities in mitochondrial transport that contribute to progressive neurodegeneration and irreversible disability. The current methodologies to study mitochondria are limiting and are capable of providing only a partial snapshot of the true mitochondria activity at a particular timepoint during disease. Mitochondrial functional studies are mostly performed in cell culture or whole brain tissue, which prevents understanding of mitochondrial pathology in distinct cell types in vivo. A true understanding of cell-specific mitochondrial pathophysiology of MS in mouse models is required. Cell-specific mitochondria morphology, mitochondria motility, and ATP production studies in animal models of MS will help us understand the role of mitochondria in the normal and diseased CNS. In this review, we present currently used methods to investigate mitochondria function in MS mouse models and discuss the current advantages and caveats with using each technique. In addition, we present recently developed mitochondria transgenic mouse lines expressing Cre under the control of CNS specific promoters to relate mitochondria to disease in vivo.